The relationship of the family planning program in suppressing population growth in maginti village, maginti district, west muna regency - Suhartini; Muliyana; B.P, Delfiani; Azis, Reskiawati; Taher, Rusli; Eppang, Yudiarsi (CV. Paperhome Indonesia, 2025)
Background: Population is one of the most important indicators in a country. Classical economists, pioneered by Adam Smith, even considered that population was a potential input that could be used as a factor of production to increase the output of a corporate household. The more people there are, the more labor that can be used. The Purpose Of This Study Is To Know The Relationship Of Knowledge And Access To Information With To Know The Relationship Of KB Programs In Suppressing Population Growth Rate In Maginti Village Of Maginti District Of West Muna Regency In 2023 Methods: This study used a descriptive survey research design correlated with the Cross Sectional approach, a sample of 45 respondents. The sampling technique used is accidental sampling Results: Based on table 5.4 above, it was obtained that out of 45 respondents, there were 8 (17.8%) respondents who stated that the birth control program was beneficial but the population growth rate was rapid, and there were 25 (55.6%) respondents who stated that the birth control program was beneficial along with evidence that the population growth rate was lagging. While the respondents who stated that the KB program was not beneficial, there were 8 (17.8%) accompanied by a rapid population growth rate, and there were 4 (8.9%) respondents who stated that the KB program was not beneficial, but the population growth rate was delayed. Based on the results of Chi-Square statistical test, it was obtained that the ρ value of 0.009 means that there is a Relationship of KB Programs In Suppressing Population Growth Rate In Maginti Village Of Maginti District Of West Muna Regency In 2023 Conclusion : there is a Relationship between the KB Program in Suppressing the Population Growth Rate In Maginti Village of Maginti District of West Muna Regency in 2023